2009
DOI: 10.1182/blood-2008-09-180687
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic effects of targeting αIIbβ3 signaling in platelets

Abstract: alphaIIbbeta3 interaction with fibrinogen promotes Src-dependent platelet spreading in vitro. To determine the consequences of this outside-in signaling pathway in vivo, a "beta3(Delta760-762)" knockin mouse was generated that lacked the 3 C-terminal beta3 residues (arginine-glycine-threonine [RGT]) necessary for alphaIIbbeta3 interaction with c-Src, but retained beta3 residues necessary for talin-dependent fibrinogen binding. beta3(Delta760-762) mice were compared with wild-type beta3(+/+) littermates, beta3(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 51 publications
(93 reference statements)
5
59
0
Order By: Relevance
“…Studies in human platelets (2,27) and in mouse models (28,29) have revealed an essential role for Src and/or Src-␣ IIb ␤ 3 interaction in outside-in ␣ IIb ␤ 3 integrin signaling dependent functions like adhesion, and spreading on fibrinogen. We observed that PP2Ac␣-depleted cells exhibited Src activation and increased adhesion to fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in human platelets (2,27) and in mouse models (28,29) have revealed an essential role for Src and/or Src-␣ IIb ␤ 3 interaction in outside-in ␣ IIb ␤ 3 integrin signaling dependent functions like adhesion, and spreading on fibrinogen. We observed that PP2Ac␣-depleted cells exhibited Src activation and increased adhesion to fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
“…19 Furthermore, it was shown that the C-terminal end of integrin ␤3 with the sequence R 760 GT 762 mediates a direct interaction with the SH3 domain of c-Src. 20,24,25 Contrary to the canonical SH3 domain ligands with a typical poly-Pro type II helix, 11,26,27 the integrin binding motif is much shorter and does not contain a proline residue. Recently, an in vitro study using synthetic peptides corresponding to the cytoplasmic tail of integrin showed that the sequence motif RGT can selectively inhibit outside-in signaling in human platelets.…”
Section: Introductionmentioning
confidence: 94%
“…24 This together with the in vivo study using knock-in mouse suggested that peptidomimetics derived from the RGT moiety might be promising thrombosis drug candidates with little side effect toward the normal function of platelet. 25 Furthermore, the complex of c-Src:␤3 was also reported as an "oncogenic unit" promoting tumor growth and metastasis. 28,29 Hence, these observations have led to the proposal and expectation that the interaction of c-Src:␤3 could serve as an interesting therapeutic target, and better understanding of this interaction might lead to the discovery of new antithrombotic and anticancer strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Although many current therapeutic strategies are aimed at blocking integrin association with ligands, there is a recent appreciation that an alternative strategy may be to target intracellular signalling mechanisms to inhibit integrin activation, thereby suppressing ligand binding, or to prevent the downstream sequela of integrin activation 116,[163][164][165] . Potential strategies are focused on the short cytoplasmic tails of the integrin α and β subunits, although there is also evidence that the transmembrane domains may play a role [103][104]166 .…”
Section: Receptor Antagonists That Do Not Induce Conformational Changmentioning
confidence: 99%